2017
DOI: 10.3389/fphys.2017.00776
|View full text |Cite
|
Sign up to set email alerts
|

PTH Reloaded: A New Evolutionary Perspective

Abstract: The parathyroid hormone (PTH) family is a group of structurally-related secreted peptides involved in bone mineral homeostasis and multitude of developmental processes in vertebrates. These peptides mediate actions through PTH receptors (PTHRs), which belong to the transmembrane G protein-coupled receptor group. To date, genes encoding for PTH and PTHR have only been identified in chordates, suggesting that this signaling pathway may be an evolutionary innovation of our phylum. In vertebrates, we found up to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Multiple PTH receptors in different phyla of vertebrates are known to be the consequence of multiple gene duplications and losses [7,8]. Likewise, the ligand PTH also has undergone gene duplication and losses in vertebrates [9]. The PTH receptor lineage is traceable to before the time of the deuterostome-protostome split in the basal Bilateria [10][11][12], but there are no obvious homologous PTH ligands in the basal protostome lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple PTH receptors in different phyla of vertebrates are known to be the consequence of multiple gene duplications and losses [7,8]. Likewise, the ligand PTH also has undergone gene duplication and losses in vertebrates [9]. The PTH receptor lineage is traceable to before the time of the deuterostome-protostome split in the basal Bilateria [10][11][12], but there are no obvious homologous PTH ligands in the basal protostome lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Parathyroid hormone acts as regulator of hydroxylapatite formation for bone mineralisation and plays a key role in the homeostasis of Ca and P (Suarez‐Bregua, Cal, Cañestro, & Rotllant, ) by increasing serum Ca concentration and renal P excretion (Forrester & Moreland, ). It has been demonstrated that dietary P restriction not only prevents secondary hyperparathyroidism independent of serum iCa and 1,25‐(OH) 2 D 3 but also prevents parathyroid cell growth (Slatopolsky et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…We found neurons expressing tuberoinfundibular peptide of 39 residues (TIP39) in the same location (Dobolyi et al, 2003b) (Figure 3B). TIP39 belongs to the parathyroid hormone family of peptides, which is most abundantly expressed in the brain and is not known to play any role in calcium homeostasis as other members of the peptide family (Suarez-Bregua et al, 2017). Based on previous topographical characterization of the part of the brain expressing TIP39 (Ledoux et al, 1987), we called the position of TIP39 neurons in the medial subdivision of the posterior intralaminar complex of the thalamus (PIL) (Dobolyi et al, 2010).…”
Section: Prolactin Released In the Postpartum Period In Response To Suckling In Mammalsmentioning
confidence: 99%